Technical Assistance to Local Education Agencies A Manual for Technical Assistance Providers and Recipients - Worthen, Blaine R.; Wasatch Inst. for Research and Evaluation, Logan, UT.; Utah State Office of Education, Salt Lake City. Div. of Curriculum and Instruction ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
As a result of an evaluation of Title IV programs commissioned by the Utah State Office of Education, this manual addresses the needs of government agencies in providing technical assistance, such as proposal and report preparation or budget management, to local education agencies. Emphasis falls on the funding of technical assistance services, particularly on the relative merits of various funding sources. The following seven other issues in providing assistance are also considered, along with questions relevant to developing or operating a technical assistance system: (1) developing guidelines for technical assistance services, (2) identifying and maintaining a pool of qualified technical assistance personnel, (3) encouraging client agencies to use assistance programs, (4) keeping records of assistance requests, (5) delivering technical assistance to suit clients' needs, (6) evaluating assistance programs, and (7) providing models for local agency initiatives. Appendixes include a set of sample guidelines for services, samples of memoranda and forms requesting and logging technical assistance, and examples of acceptable final reports to the state from local agencies. (JW)
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Consultation Programs; Elementary Secondary Education; Models; Program Development; School Districts; State School District Relationship; Technical Assistance; Utah; Guides, Non-Classroom.